ACTIVITY TEST OF A LIQUID HAND SANITIZER WITH LIME EXTRACT (CITRUS AURANTIFOLIA) AND ALOE VERA (ALOE VERA) AGAINST ESCHERICHIA COLI BACTERIA - Lukky Jayadi; Sandry Kesuma (Jurnal Farmasi Sains dan Praktis, 2021)
One of the ways to prevent the spread of disease is to clean your hands using a hand sanitizer. Hand sanitizers are currently sterile hand sanitizers, usually as an alternative to washing the skin surface with a cleanser and air. Washing hands and skin with hand sanitizer is an action to maintain hand and skin hygiene to avoid infection that causes microbes, for example Escherichia coli microorganisms. The purpose behind this examination is make liquid hand sanitizer preparations with lime (Citrus aurantifolia) and aloe vera (Aloe vera) extracts that can kill Escherichia coli bacteria. In this study, the pH of the preparation was measured, the pH was 5 and for determining the specific gravity, the specific gravity was 0.9736 g/ml. The test is carried out using the percentage kill method at two contact times, namely 30 and 60 seconds. The percentage kill results for liquid hand sanitizer with lime (Citrus aurantifolia) and aloe vera (Aloe vera) extracts at the two contact times, with a percentage kill value of 99.9%. There is an impact using hand sanitizer with alcohol as an active ingredient with active alcohol ingredients with the addition of lime extract (Citrus aurantifolia) and aloe vera (Aloe vera) on pH, specific gravity and germicidal power.